TRANSLATION OF IDIOMS AND FIXED EXPRESSIONS: STRATEGIES AND DIFFICULTIES - Sharifjonova Mokhiyat Sherzod qizi (TADQIQOTLAR.UZ, 2024)
This study aims to examine and initially identify some of the current barriers that arise when translating interlingual idiomatic pairings, and then to propose some important theoretical solutions to these problems. The current study attempts to examine these classifications and implement them in practice, drawing on Mona Baker's (1992) classification of challenges and tactics and the corresponding subcategories described. Them mostly for a few pairs in English and the corresponding Turkish and Persian. Results indicate that Correct translation of colloquial terms requires careful consideration of several variables.